Draft Genome Sequence of Shewanella sp. Strain ISO12, a Candidate Probiotic Isolated from the Intestine of Fundulus heteroclitus - Schreier, Harold J. (Microbiol Resour Announc, 2020)
The genome of Shewanella sp. strain ISO12, which was isolated from the intestine of wild-caught Fundulus heteroclitus, was sequenced and is reported here. Bioinformatic analysis revealed genes encoding the bacteriocin marinocine and those potentially associated with probiotic activity. The genome sequence will assist in further identifying probiotic and other antibacterial processes.